Հայ մշակութային ինքնութեան իմաստաւորումը Գարեգին Լեւոնեանի «Գեղարուեստ» ամսագրում - Պետրոսեան, Դաւիթ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье журнала Г. Левоняна «Гегарвест» рассматривается ряд вопросов, касающихся армянской культурной идентичности. В основе исследования лежит раздел журнала «История искусства», предоставляющий широкий спектр возможностей для осмысливания армянской культуры в историческом пространстве и времени. Предпринята попытка выявить компоненты армянской культурной идентичности с особым акцентом на пространственные виды искусства (архитектура, миниатюра) и музыку. Исторические слтих видов искусства были рассмотрены также в контексте трансформации идентичность-несхожесть. The article addresses a number of issues related to the Armenian cultural identity in G. Levonyan’s journal “Gegharvest”. The study focuses on the section of the journal “History of Art”, which provides a wide range of opportunities for understanding the Armenian culture in the prospect of historical space and time. An attempt was made to discover the components of the Armenian cultural identity with a special emphasis on spatial arts (architecture, miniature) and music.The historical layers of these forms of art were also considered in the context of identity-dissimilarity transformation․
Keywords: Periodicals; Culture and Cultural Processes